Wayside wheel-rail vertical contact force continuous detecting method and its application. (April 2022) - Peng, Xinyu; Zeng, Jing; Wang, Jianbin; Wang, Qunsheng; Li, Dadi; Liang, Songkang
Highlights: A continuous wheel/rail force measuring method is investigated. An indoor prototype is built for verification. The 14-span discrete wheel/rail force can completely cover the detected wheel surface and reflect the wheel faults. A calibration device which can move easily on the track was proposed. The impact signal of wheel flat collected by indoor prototype shows a strong regularity, study on the relationships can provide basis for wheel fault diagnosis. Abstract: In order to obtain more reliable wheel-rail contact force and improve the accuracy of wheel fault detection, a continuous wheel/rail force measuring method is investigated, and an indoor prototype is built for verification. The wheel/rail force is mainly measured by shear method, and the time of wheel entering and leaving the test area is measured by proximity switch at the same time. Then the measured discrete wheel/rail forces are connected together by computer editing. The calibration coefficients of the shear wheel/rail forces can be obtained by using a special calibration device which can move easily on the rails. The results show that the continuous wheel/rail force reproduced by using 14 measured discrete wheel/rail forces can cover the whole wheel running surface, and also can reflect the wheel surface defects. When the wheel defect such as wheel flat appears, the wheel/rail impact induced by wheel flat has a strong effect on the wheel/rail force. Thus the mapping relationship between the wheel flat and wheel/rail force can be established and be adopted to identify the length and depth of wheel flat.